Towards a geopolitics of atheism: Critical geopolitics post the 'War on Terror'. (September 2017) - Foster, Russell; Megoran, Nick; Dunn, Michael
Abstract: Political geography has an established tradition of engaging with religiously-driven geopolitik . However, despite the remarkable growth in professed atheist beliefs in recent decades and the popular expression of an imagined geopolitical binary between secular/atheist and religious societies, the geopolitics of irreligion have received almost no attention among academic practitioners. This paper outlines the core tenets of 'New Atheist' philosophy, before addressing how its key representatives have taken positions on the 'Global War on Terror.' In particular, we critically interrogate the works of Richard Dawkins, Sam Harris, and the late Christopher Hitchens and identify a belligerent geopolitical imagination which posits a civilizational clash between an existentially-threatened secular, liberal West with responsibility to use extraordinary violence to protect itself and the world from a backwards oriental Islam. The paper concludes with four possible explanations for the paradox that the New Atheist critique of religion for being violent acts itself as a geopolitical incitement to violence. In so doing, we seek to navigate debates about the nature and purpose of critical geopolitical research given that the historical, intellectual and political contexts in which it was formed have changed.